Coding and educational robotics with peers: The C0D1NC experience to foster inclusion - Ponticorvo, Michela; Rubinacci, Franco; Dell’Aquila, Elena; Marocco, Davide (Frontiers in Robotics and AI, 2022)
In the present paper, the experience of the C0D1NC project (Coding for inclusion) is described. In this project an innovative methodology based on peer-education is the core of the educational approach. High school students become "teachers" as they are trained to teach coding and robotics to younger students. This approach favors inclusion and digital inclusion. To affirm this, we evaluated different aspects: relations between peers, perceived self-efficacy, and attitude towards technology at the beginning of activities (pre-test) and the end (post-test). Results indicate that this approach can be effective to foster the acquisition and strengthening of skills in coding, robotic and computational thinking and to favor personal growth, improved relations between peers, and increased self-efficacy too.